The sinking of the Titanic, 1912 - Tarshis, Lauren; Dawson, Scott (New York : Scholastic, 2010)
Excited to board the Titanic with his aunt and little sister, ten-year-old George begins to explore the ill- fated ship's first-class storage cabin when the ship is rocked by a collision with an iceberg and begins to sink.
590
Accelerated Reader AR
Keywords: Titanic (Steamship) -- Juvenile fiction; Ocean travel -- Juvenile fiction; Shipwrecks -- Juvenile fiction; Adventure stories; Historical fiction